Innovation beyond technology: perspectives from Latin America. Issue 4 (6th November 2017) - Zawislak, Paulo Antônio; Tello-Gamarra, Jorge; Fracasso, Edi Madalena; Castellanos, Oscar
Abstract : Purpose: The purpose of this paper is to present eight papers selected from ALTEC 2015 that provide an overview of innovation in Latin America. Design/methodology/approach: This editorial seeks to define innovation by examining its conceptual foundations. It considers innovation beyond firms and technology to address other forms, such as social and institutional innovations. Thereafter, it discusses innovation in the context of Latin America and suggests means by which to stimulate it in the region. Finally, the authors present the eight papers included in this "special edition." Findings: The major findings of the paper are that it considers non-technological innovation within firms, innovation beyond the firm and innovation beyond technology. Moreover, it helps to better understand a core issue of innovation in Latin America, which is the focus on macroeconomic policy instead of microeconomic stimuli. Originality/value: A broader understanding of the concept of innovation is of notable importance. Innovation implies the recognition of issues related to the market (firm), but also to the community (society) and to humanly devised constraints (institutions). Technology is only one part of it. For this special issue, the selected articles highlight the efforts made by different authors to contribute to innovation studies in the editors' region. Abstract : Propuesta: Este número presenta ocho manuscritos seleccionados del ALTEC 2015, que ofrecen un panorama de la innovación en América Latina. Diseño/metodología/enfoque: Esta editorial busca definir la innovación mediante la examinación de sus fundamentos conceptuales. Esto considera que la innovación va más allá de las firmas y la tecnología para abordar otros tipos, tales como innovación social e institucional. Posteriormente, se analiza la innovación en el contexto de América Latina y se sugieren medios para su estimulo en la región. Finalmente, presentamos los ocho artículos incluidos en esta Edición Especial. Resultados: Las principales conclusiones de esta editorial son que se considera la innovación no tecnológica dentro de las firmas, la innovación más allá de la firma y la innovación más allá de la tecnología. Además, esto ayuda a comprehender mejor una cuestión central de la innovación en América Latina, que es el enfoque en política macroeconómica en lugar de los estímulos microeconómicos. Originalidad/valor: Un mayor entendimiento del concepto de innovación es de gran importancia. La innovación implica el reconocimiento de las cuestiones relacionadas con el mercado (firma), pero también con la comunidad (sociedad) y con las restricciones humanamente concebidas (instituciones). La tecnología es solo una parte de esta. Para esta Edición Especial, los artículos seleccionados destacan los esfuerzos realizados por diferentes autores para contribuir a los estudios de innovación en nuestra región.